The Influence Of Debt To Equity Ratio, Return On Equity, And Return On Investment On Stock Returns On Non-Cyclicals Consumer Sub-Sector Companies Listed On The Indonesia Stock Exchange For The Period 2016-2020 - Jose Putra Mahendra (EMaBi: Ekonomi Dan Manajemen Bisnis, 2022)
Investment is an activity that can involve and can be done by anyone to generate profits in an industry. This study has a purpose, the purpose is to test the influence of DER, ROE, and ROI on Stock Returns on non-cyclicals consumer subsector companies listed on the Indonesian Stock Exchange period of 2016-2020, both partially and simultaneously. In this study, the authors used quantitative methods. The data used is secondary, sampling was performed by using a purposive sampling technique with a sample count of 6 companies over a 5-year period of consecutive observations, resulting in a total sampling of 30. The results give information that the variables have simultaneous influence between DER, ROE, and ROI. Partially, there are a significant influence between DER and ROE on Stock Returns, whereas one other variable, namely, ROI does not have a significant effect on stock returns.